Orientering i politikens terräng: En studie av regeringsavtal som karta för regleringsbrev - Thomasson,Ester; Ahlqvist,Fanny (2025)
The two most recent parliamentary elections in Sweden were followed by intense negotiation and remarkable long periods of time before government formation. This culminated in comprehensive agreements between the government parties and supporting parties. The January Agreement was the foundation for Stefan Löfven’s government (Januariavtalet, 2019), and the Tidö Agreement is the foundation for Ulf Kristersson’s current government (Tidöavtalet, 2022). Do these contractually bound governments affect the governance of Swedish government agencies? In this essay we explore if these agreements cause a more excessive regulation in the government’s appropriation directives to two selected agencies. We also investigate in what way the agreements are reflected in the directives. Given the context of extensive agreements in Sweden, the study adopts a case study approach. It also incorporates elements of content analysis, as appropriation directives are a type of text. Furthermore the Principal-Agent-Theory and Coalition Theory is used to help explain how the government manages their agencies and how these agreements alter the political landscape when it comes to government formation. More excessive regulation in the appropriation directives are mainly confirmed, however there is not definitive support that the agreements cause this. Nonetheless the agreements are clearly reflected in the appropriation directives.
Keywords: myndighetsstyrning; regleringsbrev; avtalsregering; Januariavtalet; Tidöavtalet